Surface EMG based controller design for knee rehabilitation devices - Jutamanee Poonsiri (2018)
People with a knee contracture can experience mobility problems. One method to prevent the contracture is to have a range of motion exercise. This can be performed with the help of a caregiver or by external devices. The focus of this paper is to design a controller which can be implemented with the active knee exercising system. Surface electromyography (EMG) is taken from the quadriceps and the bicepfemoris muscles from different angles of the knee. The surface EMG is the input information for the controller to generate flexible and smooth motions. Changes of EMG signal levels are defined, and the intended knee angle is estimated by using the fuzzy logic method. The experimental results show that the sEMG data can be used to estimate the knee flexion and extension angle. © 2011 IEEE.